(untitled) (International Journal of Engineering and Computer Science, 2017)
In this system, the customer has the benefit to shop online in a smart way by trying on different accessories like sunglasses, hat, necklaces, etc using webcam. In order to place the clicked image on the face or other body part automatically, face detection algorithm like Viola-Jones is used. Thus the presence of this unique feature enhances the system and stands out as completely different website amongst other existing websites.